Development of Snacks (Murukku) by Incorporation of Broiler Skin - Mandal, P.K.; Cytyarasan, S.; Pal, U. K.; Rao , V. K.; Das, C. D. (Journal of Meat Science, 2011)
About 505 millions of broiler chickens are annually slaughtered in India of which skin contribute 14% of the dressed weight. Proper utilization of skin will open avenue for its economic disposal. Therefore, this study was planned to prepare snacks by using broiler skin to assess their comparative quality. A recipe for snacks (muruku) was standardized containing rice flour, black gram, salt, dry spices, sesame seed (till), oil at 90, 10, 1.75, 1, 1, and 3%, respectively. The standardized recipe was taken as control and raw chicken skin was incorporated in that at 15 and 30 % levels. The snacks were prepared by hand mixing of all the ingredients with water and deep oil fried at 130°C for 5 min. The physico-chemical and sensory quality of the snacks were assessed. The moisture, protein, fat were 6.60, 5.33, 6.77; 13.18, 13.34, 13.49; 6.98, 8.35, 11.24 percent, respectively. Fat content was significantly (p<0.05) higher in snacks prepared with 30% broiler skin. Organoleptically the snack with 15% broiler skin was found to be more acceptable than the other two products. Preparation of snacks by incorporation of broiler skin could be a novel approach for economic utilization of poultry skin.